Anti-corrosion epoxy mortar, preparation method thereof and application of anti-corrosion epoxy mortar in anaerobic concrete pool
By using porous powder quartz in epoxy mortar and adsorption accelerator, the corrosion problem of anaerobic concrete pools in sewage treatment facilities is solved, and higher adhesion, adhesion and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202510016312.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-29
AI Technical Summary
Anaerobic concrete pools are susceptible to corrosion in sewage treatment facilities, and the existing epoxy mortars are insufficient in this environment.
Porous powder quartz is used as filler, and 1,3-dimethylurea and 2,4,6-tris(dimethylaminomethyl)phenol are adsorbed on its surface to improve the adhesion, adhesion and solidification rate of epoxy mortar.
It significantly improves the adhesion and adhesion of epoxy mortar on the concrete surface, enhances its corrosion resistance in an anaerobic environment, and extends the service life of the concrete pool.
Abstract
Description
Technical Field
[0001] The invention relates to the field of concrete, in particular to anticorrosive epoxy mortar and a preparation method thereof and application thereof in anaerobic concrete pools. Background Art
[0002] Epoxy mortar has become an ideal material for solving concrete corrosion problems due to its excellent chemical resistance, adhesion, impact resistance and durability. For example, patent CN107628779A discloses an environmentally friendly concrete water-based epoxy repair mortar, which is prepared as follows: take bisphenol A epoxy resin and C12-14 alkyl glycidyl ether, mix to form component A; take non-ionic modified polyamine curing agent, wetting agent and defoamer, mix and disperse evenly to obtain component B; take two quartz sands of different particle sizes and mix them into a sand material mixture; mix cement and sand material mixture evenly to obtain sand material raw material; mix component A and component B, stir to obtain a paste; add one-third of tap water to the paste, stir evenly, add the remaining tap water, stir evenly to obtain epoxy resin mixed liquid; mix the sand material raw material and epoxy resin mixed liquid, stir evenly to obtain environmentally friendly concrete water-based epoxy repair mortar. The repair mortar does not use organic solvents, thus avoiding environmental pollution and potential safety hazards. It does not affect the performance of existing materials when used, meets the requirements for concrete repair, and does not require high-level treatment of the base layer.
[0003] With the rapid development of the sewage treatment industry, closed concrete structures are widely used in sewage treatment plants, chemical plants, industrial wastewater treatment facilities, etc. The concrete pools in these facilities are more susceptible to corrosion, especially in anaerobic environments. Therefore, it is necessary to further modify the epoxy mortar to improve its corrosion resistance and other properties. Summary of the invention
[0004] The invention provides an anticorrosive epoxy mortar and a preparation method thereof and an application of the mortar in an anaerobic concrete water tank. The epoxy mortar contains porous powdered quartz with multiple hydroxy groups, so that the adhesion and bonding of the epoxy mortar on the concrete surface are improved, and 1,3-dimethylurea and 2,4,6-tris(dimethylaminomethyl)phenol are adsorbed in the porous powdered quartz to improve the dispersibility of the accelerator, thereby increasing the solidification rate and density of the epoxy mortar on the concrete surface.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The anticorrosive epoxy mortar comprises component A and component B. Component A comprises epoxy resin, filler and additives, and component B comprises an amine curing agent and porous powdered quartz. The porous powdered quartz adsorbs 1,3-dimethylurea and 2,4,6-tris(dimethylaminomethyl)phenol. The particle size of the filler is 40-100 μm, and the particle size of the porous powdered quartz is 3-10 μm.
[0006] Preferably, the filler is selected from one or more of mica powder and talc powder.
[0007] Preferably, the auxiliary agent includes a diluent and a plasticizer, wherein the diluent is selected from one or more of acetone, benzene, toluene and xylene; and the plasticizer is selected from one or more of dibutyl phthalate and dioctyl phthalate.
[0008] Preferably, the amine curing agent is selected from one or more of diethylenetriamine, triethylenetetramine and isophoronediamine.
[0009] Preferably, the porous powdered quartz has a pore size of 8-10 nm and a porosity of 35-45%.
[0010] Preferably, the mass parts of component A are: 100 parts of epoxy resin, 100-200 parts of filler, 10-15 parts of diluent, and 6-8 parts of plasticizer.
[0011] Preferably, the mass fractions of component B are: 5-10 parts of amine curing agent and 20-50 parts of porous powder quartz. The adsorption amount of 1,3-dimethylurea and 2,4,6-tris(dimethylaminomethyl)phenol in porous powder quartz is 0.5-5g / 100g.
[0012] Preferably, the mass ratio of component A to component B is 10-20:1.
[0013] Preferably, 0.5-2 parts of 1,3-dimethylurea and 1-3 parts of 2,4,6-tris(dimethylaminomethyl)phenol are added for every 100 parts of epoxy resin.
[0014] The present invention also provides a method for preparing the anticorrosive epoxy mortar, comprising the following steps: (1) mixing epoxy resin, filler and additives uniformly to obtain component A; (2) preparing a solution of 1,3-dimethylurea, immersing porous powder quartz therein, taking it out and drying it, thereby obtaining porous powder quartz I that adsorbs 1,3-dimethylurea; preparing a solution of 2,4,6-tris(dimethylaminomethyl)phenol, immersing porous powder quartz therein, taking it out and drying it, thereby obtaining porous powder quartz II that adsorbs 2,4,6-tris(dimethylaminomethyl)phenol; When in use, first add porous powder quartz 1 and porous powder quartz 2 to component A and mix evenly, then add amine curing agent and mix evenly.
[0015] The invention also provides application of the anticorrosive epoxy mortar in an anaerobic concrete pool.
[0016] Therefore, the beneficial effects of the present invention are: (1) Use porous powder quartz in mortar, and limit the particle size of porous powder quartz to be much smaller than the filler. The fine particle grading has good fluidity, allowing porous powder quartz to fill small gaps and improve the density of the coating.
[0017] (2) Porous powdered quartz contains hydroxyl groups, which can improve the adhesion and bonding of epoxy mortar on the concrete surface.
[0018] (3) Porous powder quartz adsorbs 1,3-dimethylurea and 2,4,6-tris(dimethylaminomethyl)phenol, causing them to be more evenly dispersed in the mortar; the capillary effect of porous powder quartz can also allow the amine curing agent to contact the accelerator faster and exert a curing effect. DETAILED DESCRIPTION
[0019] The technical solution of the present invention is further described below through specific embodiments.
[0020] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art. Unless otherwise specified, parts are all weight parts, temperatures are expressed in ° C or at ambient temperature, and pressures are atmospheric pressure or near atmospheric pressure. There are many variations and combinations of reaction conditions (such as component concentrations, desired solvents, solvent mixtures, temperatures, pressures, and other reaction ranges) and conditions that can be used to optimize the purity and yield of the product obtained by the method, and only reasonable routine experiments will be required to optimize such method conditions.
[0021] Example In the urban sewage treatment system, the sewage pipes, storage tanks, treatment tanks, etc. that transport and treat sewage are all reinforced concrete structures. These structures are generally buried, semi-buried, closed, semi-closed or open in the open air. They are subject to long-term rain erosion, ion penetration, microbial corrosion and other corrosion effects, and the structure is easily damaged. Among them, the corrosion damage of concrete microorganisms is one of the important reasons for the deterioration of sewage system structure, which seriously affects the service life of concrete structures.
[0022] In an anaerobic environment, concrete structures in sewage treatment facilities are more susceptible to corrosion. The organic and inorganic acids produced by anaerobic bacteria metabolism react with calcium hydroxide in concrete, destroying the structure of CSH gel in cement, affecting the normal hydration process of concrete, and thus causing concrete strength to decrease, or even serious structural damage. This type of corrosion not only shortens the service life of sewage treatment facilities, but also increases the cost of maintenance and replacement, posing a threat to the normal operation of sewage treatment plants. An ideal solution is needed.
[0023] Epoxy mortar has become an ideal material for solving concrete corrosion problems due to its excellent chemical resistance, adhesion, impact resistance and durability. It can effectively resist the erosion of acidic, alkaline substances and other corrosive chemicals in sewage, while providing a solid protective layer for concrete. Compared with traditional anti-corrosion technologies such as silicate coatings and glass flake coatings, epoxy mortar has significant advantages in chemical resistance and mechanical strength. Traditional silicate coatings have poor tolerance to acid and alkaline environments and are prone to aging and cracking, while epoxy mortar can maintain a long service life in highly corrosive anaerobic environments. Although glass flake coatings also have good corrosion resistance, their adhesion is often not as good as epoxy mortar, and the construction process is more complicated and the cost is relatively high. The ease of construction and superior durability of epoxy mortar enable it to significantly reduce long-term maintenance costs. Therefore, in anaerobic environments, the anti-corrosion performance of epoxy mortar is significantly better than that of traditional materials, which can extend the service life of concrete pools and reduce the need for frequent maintenance and repairs. This not only reduces operating costs, but also improves the overall operating efficiency of sewage treatment facilities.
[0024] The invention provides an anticorrosive epoxy mortar. Porous powder quartz containing hydroxyl groups on the surface is added into the formula to improve the adhesion and bonding of the epoxy mortar on the concrete surface. Accelerators 1,3-dimethylurea and 2,4,6-tris(dimethylaminomethyl)phenol are adsorbed into the porous powder quartz to improve the dispersibility of the accelerators and improve the solidification rate and density of the epoxy mortar on the concrete surface.
[0025] 1. An anticorrosive epoxy mortar The invention comprises component A and component B in a mass ratio of 10-20:1.
[0026] Component A includes 100 parts of epoxy resin, 100-200 parts of filler, and 16-23 parts of additives by mass. Among them, the epoxy resin is preferably a glycidyl ether epoxy resin, and more preferably a bisphenol A epoxy resin. The filler is selected from one or more of mica powder and talcum powder, and the particle size of the filler is 40-100 μm. The additives are 10-15 parts of diluent and 6-8 parts of plasticizer, and the diluent is selected from one or more of acetone, benzene, toluene, and xylene; the plasticizer is selected from one or more of dibutyl phthalate and dioctyl phthalate.
[0027] In terms of mass fraction, component B contains 5-10 parts of amine curing agent and 20-50 parts of porous powder quartz. The amine curing agent is selected from one or more of diethylenetriamine, triethylenetetramine and isophoronediamine. The particle size of porous powder quartz is 3-10μm, the pore size is 8-10nm, and the porosity is 35-45%. The porous powder quartz adsorbs 1,3-dimethylurea and 2,4,6-tris(dimethylaminomethyl)phenol, and the total adsorption amount of 1,3-dimethylurea and 2,4,6-tris(dimethylaminomethyl)phenol in the porous powder quartz is 0.5-5g / 100g.
[0028] Porous quartz is a volcanic sedimentary rock with fine natural particle size, uniform particle distribution and large specific surface area (8.3m 2 / g), the external structure is approximately spherical and has no edges and corners. From the electron microscope image, its surface is full of nano-scale mesopores. It has both the hardness of quartz and the lightness and adsorption of diatomaceous earth, so that it has good fluidity in polymer composite materials, which is conducive to processing. The advantages of using porous powder quartz in the present invention are: using porous powder quartz in mortar can play a role in fine particle grading and has good fluidity; the surface of porous powder quartz contains hydroxyl groups, which helps to improve the adhesion and bonding of epoxy mortar on the concrete surface; the promoter can help amine curing agent and epoxy group to react and cure quickly, but the efficiency is greatly affected by the dispersion uniformity of the three. By using the porous adsorption promoters 1,3-dimethylurea and 2,4,6-tris(dimethylaminomethyl)phenol of porous powder quartz, the porous powder quartz has good dispersibility in the mortar, which drives the promoter to be more evenly dispersed in the mortar; the capillary effect of porous powder quartz can also allow the amine curing agent to contact with the promoter faster to play a curing effect.
[0029] Based on the above principles, the present invention also defines: (1) The particle size of porous powder quartz is much smaller than that of the filler, so that the porous powder quartz fills small gaps and improves the density of the coating. (2) The promoter is selected to contain a benzene ring and a multi-branched structure. Part of the branched chain of the promoter extends into the pores of the porous powder quartz and is adsorbed. The presence of the benzene ring prevents it from completely entering the pores, and at least part of the active branched chain (including N branched chain) is exposed to the outside to play a promoting role.
[0030] 2. A method for preparing anticorrosive epoxy mortar The present invention also provides a method for preparing the anticorrosive epoxy mortar, comprising the following steps: (1) 100 parts of epoxy resin, 100-200 parts of filler and 16-23 parts of auxiliary agent are mixed uniformly to obtain component A; (2) dissolving 0.5-2 parts of 1,3-dimethylurea in water to obtain a solution, dipping porous powder quartz in the solution, taking out and drying, to obtain porous powder quartz I that adsorbs 1,3-dimethylurea; dissolving 1-3 parts of 2,4,6-tris(dimethylaminomethyl)phenol in ethanol to obtain a solution, dipping porous powder quartz in the solution, taking out and drying, to obtain porous powder quartz II that adsorbs 2,4,6-tris(dimethylaminomethyl)phenol; When using, first add 20-50 parts of porous powder quartz 1 and porous powder quartz 2 to component A and mix evenly, then add 5-10 parts The amine curing agent is mixed evenly to obtain the anticorrosive epoxy mortar.
[0031] 3. Application of anti-corrosion epoxy mortar in anaerobic concrete pool Roughen the surface of the concrete, clean the dust, scum, and loose layers on the surface of the hole, expose the concrete body, and use a hot air blower to blow dry the contact surface to keep the surface dry. Use a putty knife to scrape the epoxy resin mortar on the surface of the hole, repair it in layers, and the scraping direction should be uniform. The construction temperature of epoxy resin mortar is 15-30℃, and the relative humidity should not be greater than 80%. When the construction environment temperature is less than 10℃, heating and insulation measures should be adopted. The prepared mortar should be used up within 30 minutes, and the curing time should not be less than 7 days. The coating thickness of the anti-corrosion epoxy mortar is 1-5mm.
[0032] Example 1 A method for preparing an anticorrosive epoxy mortar, comprising the following steps: (1) 100 parts of bisphenol A epoxy resin, 150 parts of mica powder (average particle size 50 μm), 12 parts of acetone and 7 parts of dibutyl phthalate were uniformly mixed to obtain component A; (2) dissolving 1 part of 1,3-dimethylurea in water to obtain a solution, and immersing 20 parts of porous powder quartz (particle size 5 μm, pore size 9 nm, porosity 35-45%) therein, taking out and drying, to obtain porous powder quartz 1 that adsorbs 1,3-dimethylurea; dissolving 1 part of 2,4,6-tris(dimethylaminomethyl)phenol in ethanol to obtain a solution, and immersing 20 parts of porous powder quartz (particle size 5 μm, pore size 9 nm, porosity 35-45%) therein, taking out and drying, to obtain porous powder quartz 2 that adsorbs 2,4,6-tris(dimethylaminomethyl)phenol; When in use, first add porous powder quartz 1 and porous powder quartz 2 to component A and mix evenly, then add 8 parts of diethylenetriamine and mix evenly to obtain anti-corrosion epoxy mortar.
[0033] The above anti-corrosion epoxy mortar is used for anaerobic concrete pools. Specifically: roughen the surface of the concrete, clean the dust, scum, and loose layers on the surface of the holes, expose the concrete body, and use a hot air blower to blow dry the contact surface to keep the surface dry. Use a putty knife to scrape the epoxy resin mortar on the surface of the holes, repair them in layers, and the scraping direction should be uniform. The construction temperature of the epoxy resin mortar is 20℃ and the relative humidity is 60%. The prepared mortar should be used up within 30 minutes and the curing time is 7 days. The coating thickness of the anti-corrosion epoxy mortar is 3mm.
[0034] Example 2 A method for preparing an anticorrosive epoxy mortar, comprising the following steps: (1) 100 parts of bisphenol A epoxy resin, 100 parts of talc (average particle size 40 μm), 10 parts of benzene and 6 parts of dioctyl phthalate were uniformly mixed to obtain component A; (2) dissolving 0.5 parts of 1,3-dimethylurea in water to obtain a solution, and immersing 10 parts of porous powdered quartz (particle size 5 μm, pore size 9 nm, porosity 35-45%) therein, taking out and drying, to obtain porous powdered quartz I that adsorbs 1,3-dimethylurea; dissolving 1 part of 2,4,6-tris(dimethylaminomethyl)phenol in ethanol to obtain a solution, and immersing 30 parts of porous powdered quartz (particle size 5 μm, pore size 9 nm, porosity 35-45%) therein, taking out and drying, to obtain porous powdered quartz II that adsorbs 2,4,6-tris(dimethylaminomethyl)phenol; When in use, first add porous powder quartz 1 and porous powder quartz 2 to component A and mix evenly, then add 10 parts of triethylenetetramine and mix evenly to obtain anticorrosive epoxy mortar.
[0035] Example 3 A method for preparing an anticorrosive epoxy mortar, comprising the following steps: (1) 100 parts of bisphenol A epoxy resin, 200 parts of mica powder (average particle size 100 μm), 15 parts of xylene and 8 parts of dibutyl phthalate were uniformly mixed to obtain component A; (2) dissolving 0.5 parts of 1,3-dimethylurea in water to obtain a solution, and immersing 10 parts of porous powdered quartz (particle size 5 μm, pore size 9 nm, porosity 35-45%) therein, taking out and drying, to obtain porous powdered quartz I that adsorbs 1,3-dimethylurea; dissolving 2 parts of 2,4,6-tris(dimethylaminomethyl)phenol in ethanol to obtain a solution, and immersing 40 parts of porous powdered quartz (particle size 5 μm, pore size 9 nm, porosity 35-45%) therein, taking out and drying, to obtain porous powdered quartz II that adsorbs 2,4,6-tris(dimethylaminomethyl)phenol; When in use, first add porous powder quartz 1 and porous powder quartz 2 to component A and mix evenly, then add 10 parts of isophorone diamine and mix evenly to obtain anti-corrosion epoxy mortar.
[0036] Example 4 The difference from Example 1 is that the filler is a mixture of 50 parts of mica powder (average particle size 100 μm) and 100 parts of talc powder (average particle size 50 μm), specifically as follows: A method for preparing an anticorrosive epoxy mortar, comprising the following steps: (1) 100 parts of bisphenol A epoxy resin, 50 parts of mica powder (average particle size 100 μm), 100 parts of talc powder (average particle size 50 μm), 12 parts of acetone and 7 parts of dibutyl phthalate were mixed uniformly to obtain component A; (2) dissolving 1 part of 1,3-dimethylurea in water to obtain a solution, and immersing 20 parts of porous powder quartz (particle size 5 μm, pore size 9 nm, porosity 35-45%) therein, taking out and drying, to obtain porous powder quartz 1 that adsorbs 1,3-dimethylurea; dissolving 1 part of 2,4,6-tris(dimethylaminomethyl)phenol in ethanol to obtain a solution, and immersing 20 parts of porous powder quartz (particle size 5 μm, pore size 9 nm, porosity 35-45%) therein, taking out and drying, to obtain porous powder quartz 2 that adsorbs 2,4,6-tris(dimethylaminomethyl)phenol; When in use, first add porous powder quartz 1 and porous powder quartz 2 to component A and mix evenly, then add 8 parts of diethylenetriamine and mix evenly to obtain anti-corrosion epoxy mortar.
[0037] Comparative Example Comparative Example 1 The difference from Example 1 is that porous powdered quartz, 1,3-dimethylurea, and 2,4,6-tris(dimethylaminomethyl)phenol are added separately without adsorption. The details are as follows: A method for preparing an anticorrosive epoxy mortar, comprising the following steps: 100 parts of bisphenol A epoxy resin, 150 parts of mica powder (average particle size 50 μm), 12 parts of acetone and 7 parts of dibutyl phthalate were mixed uniformly to obtain component A; When in use, first add 40 parts of porous powder quartz, 1 part of 1,3-dimethylurea and 1 part of 2,4,6-tris(dimethylaminomethyl)phenol to component A and mix evenly, then add 8 parts of diethylenetriamine and mix evenly to obtain anticorrosive epoxy mortar.
[0038] Comparative Example 2 The difference from Example 1 is that the porous powdered quartz only adsorbs 2,4,6-tris(dimethylaminomethyl)phenol, but does not adsorb 1,3-dimethylurea. The details are as follows: A method for preparing an anticorrosive epoxy mortar, comprising the following steps: (1) 100 parts of bisphenol A epoxy resin, 150 parts of mica powder (average particle size 50 μm), 12 parts of acetone and 7 parts of dibutyl phthalate were uniformly mixed to obtain component A; (2) dissolving 2 parts of 2,4,6-tris(dimethylaminomethyl)phenol in ethanol to obtain a solution, and immersing 40 parts of porous powdered quartz (particle size 5 μm, pore size 9 nm, porosity 35-45%) therein, taking out and drying, to obtain porous powdered quartz II adsorbing 2,4,6-tris(dimethylaminomethyl)phenol; When in use, first add porous powder quartz into component A and mix evenly, then add 8 parts of diethylenetriamine and mix evenly to obtain anti-corrosion epoxy mortar.
[0039] Comparative Example 3 The difference from Example 1 is that the porous powdered quartz only adsorbs 1,3-dimethylurea and does not adsorb 2,4,6-tris(dimethylaminomethyl)phenol. The details are as follows: A method for preparing an anticorrosive epoxy mortar, comprising the following steps: (1) 100 parts of bisphenol A epoxy resin, 150 parts of mica powder (average particle size 50 μm), 12 parts of acetone and 7 parts of dibutyl phthalate were uniformly mixed to obtain component A; (2) dissolving 2 parts of 1,3-dimethylurea in water to obtain a solution, and immersing 40 parts of porous powder quartz (particle size 5 μm, pore size 9 nm, porosity 35-45%) in the solution, taking out and drying to obtain porous powder quartz 1 adsorbing 1,3-dimethylurea; When in use, first add porous powder quartz 1 to component A and mix evenly, then add 8 parts of diethylenetriamine and mix evenly to obtain anti-corrosion epoxy mortar.
[0040] Comparative Example 4 The difference from Example 1 is that the particle size of the mica powder is 20 μm. A method for preparing an anticorrosive epoxy mortar, comprising the following steps: (1) 100 parts of bisphenol A epoxy resin, 150 parts of mica powder (average particle size 20 μm), 12 parts of acetone and 7 parts of dibutyl phthalate were uniformly mixed to obtain component A; (2) dissolving 1 part of 1,3-dimethylurea in water to obtain a solution, and immersing 20 parts of porous powder quartz (particle size 5 μm, pore size 9 nm, porosity 35-45%) therein, taking out and drying, to obtain porous powder quartz 1 that adsorbs 1,3-dimethylurea; dissolving 1 part of 2,4,6-tris(dimethylaminomethyl)phenol in ethanol to obtain a solution, and immersing 20 parts of porous powder quartz (particle size 5 μm, pore size 9 nm, porosity 35-45%) therein, taking out and drying, to obtain porous powder quartz 2 that adsorbs 2,4,6-tris(dimethylaminomethyl)phenol; When in use, first add porous powder quartz 1 and porous powder quartz 2 to component A and mix evenly, then add 8 parts of diethylenetriamine and mix evenly to obtain anti-corrosion epoxy mortar.
[0041] Performance Testing The performance of the anticorrosive epoxy mortar of each embodiment and comparative example was tested, and the test methods were as follows: the test method of compressive strength was based on the standard JC / T 1041-2007; the test method of adhesion was based on the standard SY / T 0442; the test method of relative permeability was based on the standard DL / T 5150-2017; the test methods of acid resistance, alkali resistance and salt resistance were based on the standard JC / T2217-2014. The test results of acid resistance, alkali resistance and salt resistance of each embodiment showed that the coating had no cracking, no peeling and no shedding, and met the use requirements. Other results are shown in Table 1 below.
[0042] Table 1 Final setting time (min) 28D compressive strength (MPa) 28D Adhesion (MPa) <![CDATA[Relative permeability (*10 -12 cm / s) <!-- 6 -->]]> Example 1 260 93 25.1 0.221 Example 2 256 88 23.7 0.334 Example 3 273 96 28.4 0.117 Example 4 261 95 27.5 0.110 Comparative Example 1 282 82 24.0 2.681 Comparative Example 2 270 90 20.3 2.539 Comparative Example 3 272 85 19.5 3.042 Comparative Example 4 264 89 23.6 1.683
[0042] It can be seen from Table 1 that the anticorrosive epoxy mortar prepared in each embodiment of the present invention has excellent mechanical properties and anticorrosion properties, and has a fast setting time and efficient construction.
[0043] Compared with Example 1: (1) In Comparative Example 1, porous powder quartz and 1,3-dimethylurea and 2,4,6-tris(dimethylaminomethyl)phenol were added separately without adsorption, and the effect was reduced. Because the porous adsorption property of porous powder quartz was used to adsorb the adsorbent promoters 1,3-dimethylurea and 2,4,6-tris(dimethylaminomethyl)phenol, the porous powder quartz had good dispersion in the mortar, which led to a more uniform dispersion of the promoter in the mortar; the capillary effect of the porous powder quartz could also allow the amine curing agent to contact the promoter faster and exert a curing effect.
[0044] (2) Comparative Examples 2 and 3 added only one accelerator, and the effect was not as good as that of Example 1, indicating that 1,3-dimethylurea and 2,4,6-tris(dimethylaminomethyl)phenol can achieve better results when they cooperate with each other. In particular, in Comparative Example 3, only 1,3-dimethylurea was added, which was easily adsorbed in the pores of porous powdered quartz, with less active chains exposed, and the performance degradation was more serious.
[0045] (3) The particle size of the filler in Comparative Example 4 is lower than the preferred range and is close to the particle size of porous powdered quartz, and the performance of the anticorrosive epoxy mortar is reduced. The filler in Example 4 and the porous powdered quartz form a three-level particle size, which fills the gaps step by step, improves the density of the coating, and improves the performance. Therefore, the particle size has an important influence on the present invention.
[0046] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. An anticorrosive epoxy mortar, characterized in that: The invention comprises component A and component B. Component A comprises epoxy resin, filler and auxiliary agent, and component B comprises amine curing agent and porous powder quartz. The porous powder quartz adsorbs 1,3-dimethylurea and 2,4,6-tris(dimethylaminomethyl)phenol. The particle size of the filler is 40-100 μm, and the particle size of the porous powder quartz is 3-10 μm.
2. The anticorrosive epoxy mortar according to claim 1, characterized in that: The filler is selected from one or more of mica powder and talc powder.
3. The anticorrosive epoxy mortar according to claim 1 or 2, characterized in that: The auxiliary agent includes a diluent and a plasticizer. The diluent is selected from one or more of acetone, benzene, toluene and xylene; and the plasticizer is selected from one or more of dibutyl phthalate and dioctyl phthalate.
4. The anticorrosive epoxy mortar according to claim 1, characterized in that: The amine curing agent is selected from one or more of diethylenetriamine, triethylenetetramine and isophoronediamine.
5. The anticorrosive epoxy mortar according to claim 1, characterized in that: The mass proportions of component A are: 100 parts of epoxy resin, 100-200 parts of filler, 10-15 parts of diluent, and 6-8 parts of plasticizer.
6. The anticorrosive epoxy mortar according to claim 1 or 5, characterized in that: The mass proportions of component B are: 5-10 parts of amine curing agent and 20-50 parts of porous powder quartz.
7. The anticorrosive epoxy mortar according to claim 1, characterized in that: The mass ratio of component A to component B is 10-20:
1.
8. The anticorrosive epoxy mortar according to claim 1 or 7, characterized in that: For every 100 parts of epoxy resin, add 0.5-2 parts of 1,3-dimethylurea and 1-3 parts of 2,4,6-tris(dimethylaminomethyl)phenol.
9. A method for preparing the anticorrosive epoxy mortar according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Evenly mix the epoxy resin, filler and additive to obtain component A; (2) 1,3-dimethylurea is prepared into a solution, porous powder quartz is immersed in the solution, taken out and dried, and porous powder quartz 1 adsorbs 1,3-dimethylurea; 2,4,6-tris(dimethylaminomethyl)phenol is prepared into a solution, porous powder quartz is immersed in the solution, taken out and dried, and porous powder quartz 2 adsorbs 2,4,6-tris(dimethylaminomethyl)phenol is obtained; When in use, first add porous powder quartz 1 and porous powder quartz 2 to component A and mix evenly, then add amine curing agent and mix evenly.
10. Use of the anticorrosive epoxy mortar according to any one of claims 1 to 8 in an anaerobic concrete pool.
Citation Information
Patent Citations
Environment-friendly concrete water-based epoxy repair mortar
CN107628779A